2022
DOI: 10.3390/ijms23052805
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs in Cancer (Review of Literature)

Abstract: MicroRNAs (miRNAs) are short, noncoding, single-stranded RNA molecules that regulate gene expression at the post-transcriptional level by binding to mRNAs. miRNAs affect the course of processes of fundamental importance for the proper functioning of the organism. These processes include cell division, proliferation, differentiation, cell apoptosis and the formation of blood vessels. Altered expression of individual miRNAs has been shown in numerous cancers, which may indicate the oncogenic or suppressor potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 179 publications
1
61
0
7
Order By: Relevance
“…Usually, one important pathway for microRNAs (miRNAs) to result in gene silencing or translational repression was mainly contributed to binding to 3'UTR of target mRNAs (60)(61)(62). The regulatory factors of miRNA not only participate in the occurrence and development of various human tumors (63), but also show great potential in disease diagnosis, prognosis judgment and targeted therapy (64). Among them, it has been found that miRNAs are involved in differentiation, proliferation, apoptosis and other processes of leukemia cells, and its relatively specific mutational and deregulated expression profiles also have potential as diagnostic or prognostic biomarkers (65).…”
Section: Discussionmentioning
confidence: 99%
“…Usually, one important pathway for microRNAs (miRNAs) to result in gene silencing or translational repression was mainly contributed to binding to 3'UTR of target mRNAs (60)(61)(62). The regulatory factors of miRNA not only participate in the occurrence and development of various human tumors (63), but also show great potential in disease diagnosis, prognosis judgment and targeted therapy (64). Among them, it has been found that miRNAs are involved in differentiation, proliferation, apoptosis and other processes of leukemia cells, and its relatively specific mutational and deregulated expression profiles also have potential as diagnostic or prognostic biomarkers (65).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs can be easily detected in biological fluids such as blood, saliva, urine, et cetera and also detected in exosomes ( 115 ). MiRNAs have potential utility as prognostic or diagnostic biomarkers as well as therapeutic targets, and recent data also suggests miRNAs may also play a role in therapy sensitivity and/or resistance ( 116 ).…”
Section: Mirna Regulationmentioning
confidence: 99%
“…A large body of evidence has demonstrated that ncRNAs are important versatile molecules involved in various tumorigenic processes. In vivo, ncRNAs are remarkably stable and are thus potential biomarkers for the diagnosis and prognosis of cancer patients [ 17 21 ].…”
Section: Introductionmentioning
confidence: 99%